181k views
4 votes
HELLLLLLLLLLLLLLLLLLLPPPPPPPP

HELLLLLLLLLLLLLLLLLLLPPPPPPPP-example-1

2 Answers

3 votes

Answer:

Option 4 (C)

Explanation:

Substitute the f(x) = 10 - x^2 into where it says f(x):

g(x) = 3 f(x) - 8

g(x) = 3 (10-x^2) - 8

Because there is a -2 in place of the x in g(x), then we need to substitute the value of 2 for x into the equation:

g(-2) = 3 (10-(-2)^2) - 8

g(-2) = 18 - 8

g(-2) = 10

^-^ hope this helps! (●´ω`●)

5 votes

Answer:

option 4

Explanation:

User Radagast The Brown
by
4.9k points